The Actin Cytoskeleton and Actin-Based Motility - Svitkina, Tatyana (Cold Spring Harbor perspectives in biology, 2018)
The actin cytoskeleton-a collection of actin filaments with their accessory and regulatory proteins-is the primary force-generating machinery in the cell. It can produce pushing (protrusive) forces through coordinated polymerization of multiple actin filaments or pulling (contractile) forces through sliding actin filaments along bipolar filaments of myosin II. Both force types are particularly important for whole-cell migration, but they also define and change the cell shape and mechanical properties of the cell surface, drive the intracellular motility and morphogenesis of membrane organelles, and allow cells to form adhesions with each other and with the extracellular matrix.